New Perspectives on Sex Steroid and Mineralocorticoid Receptor Signaling in Cardiac Ischemic Injury - Bienvenu, Laura A.; Bell, James R.; Weeks, Kate L.; Delbridge, Lea M. D.; Young, Morag J. (Frontiers in Physiology, 2022)
The global burden of ischemic heart disease is burgeoning for both men and women. Although advances have been made, the need for new sex-specific therapies targeting key differences in cardiovascular disease outcomes in men and women remains. Mineralocorticoid receptor directed treatments have been successfully used for blood pressure control and heart failure management, and represent a potentially valuable therapeutic approach for protection from ischemic cardiac events. Clinical data indicate that mineralocorticoid excess exacerbates ischemic damage, and many of the intracellular response pathways activated in ischemia and subsequent reperfusion are regulated by mineralocorticoid receptors. In experimental contexts, where mineralocorticoid receptors are abrogated genetically or mineralocorticoid signaling is suppressed pharmacologically, ischemic injury is alleviated and reperfusion recovery is enhanced. In the chronic setting, mineralocorticoid signaling induces fibrosis, oxidative stress and inflammation, which can predispose to ischemic events and exacerbate post-myocardial infarct pathologies. Whilst a range of cardiac cell types are involved in mineralocorticoid-mediated regulation of cardiac function, cardiomyocyte-specific mineralocorticoid receptor signaling pathways are key. Selective inhibition of cardiomyocyte mineralocorticoid receptor signaling improves electromechanical resilience during ischemia and enhances contractile recovery in reperfusion. Emerging evidence suggests that mineralocorticoid receptors also contribute to sex-specific aspects of ischemic vulnerability. Indeed, mineralocorticoid receptor interactions with sex steroid receptors may differentially regulate myocardial nitric oxide bioavailability in males and females, potentially determining sex-specific post-ischemic outcomes. There is hence considerable impetus for exploration of mineralocorticoid receptor directed, cell specific therapies for both women and men in order to improve ischemic heart disease outcomes.